2003
DOI: 10.1017/s0027763000008461
|View full text |Cite
|
Sign up to set email alerts
|

On the rational solutions of q-Painlevé V equation

Abstract: Abstract. We give an explicit determinant formula for a class of rational solutions of a q-analogue of the Painlevé V equation. The entries of the determinant are given by the continuous q-Laguerre polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…It is natural to ask what kind of solutions to the Noumi-Yamada system of type A ð1Þ 5 one can get by starting with the fixed points with respect to the transformation p 3 . In this setting, we find that the system is reduced to…”
Section: Remarks and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is natural to ask what kind of solutions to the Noumi-Yamada system of type A ð1Þ 5 one can get by starting with the fixed points with respect to the transformation p 3 . In this setting, we find that the system is reduced to…”
Section: Remarks and Discussionmentioning
confidence: 99%
“…In fact, it has been revealed that the universal characters appear associated with a class of algebraic solutions to P VI and the Garnier systems [4,11]. It is also known that the rational solutions to q-P V are expressed in terms of a q-analogue of the universal characters [3].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous q-Laguerre polynomials had manifested their apparition in the rational solutions of the q-analogue of Painlevé V differential equation [9], namely as the entries of its associated determinant. They are defined by: [5] …”
Section: Continuous Q-laguerre Polynomialsmentioning
confidence: 99%
“…We often denote the q-Painlevé system (0.1) by q-P (A N −1 ). Note that q-P (A 2 ) and q-P (A 3 ) coincide with the q-Painlevé equations q-P IV and q-P V respectively; see [1,7].…”
Section: Introductionmentioning
confidence: 97%
“…As a consequence of this remarkable fact, (0.1) admits a class of rational solutions in terms of Schur polynomials; see [3] or Theorem 5.1 below. On the other hand, for the case N = 4 (q-P V ), Masuda [7] discovered another class of rational solutions which contains the former one in terms of the universal characters. Here the universal character is a generalization of Schur polynomial attached to a pair of partitions; see [5].…”
Section: Introductionmentioning
confidence: 99%